The intelligible universe an overview of the last thirteen billion years - Gonzalo, Julio A. (World Scientific Pub. Co., 2008)
This interesting book reviews WMAP's main results (2003) and discusses in detail how the accurate qualitative results for the "age" of the universe and the Hubble constant were anticipated in an article published five years before in Acta Cosmologica, Krakow. In the final chapter on "Cosmic Numbers", it is shown that, as a result of the coincidence at decoupling time between atom formation and matter/radiation equality, a reasonable cosmic justification for the mass ratio of protons and electrons is obtained